The effect of self-regulated programming learning on undergraduate students’ academic performance and motivation - Öztürk, Mücahit (Interactive technology and smart education, 2022)
Purpose>The purpose of this study was to investigate the effect of self-regulated programming learning on undergraduate students’ academic performance and motivation compared to traditional methods.Design/methodology/approach>This study was conducted with an explanatory sequential mixed method. Participants consist of 31 undergraduate students studying in the department of computer and instructional technologies education. The students were separated into two groups as experimental (n = 15) and control (n = 16) in the robotic programming course. Academic performance tests, programming motivation scale and interview form were used as data collection tools. After collecting quantitative data, interviews were conducted with the students regarding their academic performance and motivation.Findings>The results indicated that the self-regulated programming learning process can contribute positively to students’ academic performance and motivation compared to traditional methods. Students stated that self-regulated learning strategies can positively affect their academic performance and motivation.Originality/value>In this study, a self-regulated learning support system was designed to encourage students to use self-regulated learning strategies. This study has the potential to contribute to the gap in the literature, especially as a study of adapting the phased model of self-regulated learning to programming teaching. Instructors can use the self-regulating programming learning framework by adapting it to different disciplines.